Position epistemological, paradigmatical and pedagogical of the curriculum for the Degree in Nursing at the University of Costa Rica - Viriam Leiva Díaz (Universidad de Costa Rica, 2013)
We present the results of educational research which analyzed the epistemological position, paradigmatic and educational curriculum of the Degree of Nursing at the University of Costa Rica. The population consisted of the graduates of the School of Nursing. For the participation of teachers in service, worked with saturation (11). For graduates (2008) the population was 74 for a sample of 47 of them and her. We analyzed three dimensions the epistemological and pedagogical paradigm of teaching and reflected in the curriculum. To collect data, a questionnaire was structured and semi-structured interviews to selected population. The study found that although the position does not require explicit epistemic quote, there are some modules that need internal review to show consistency between what is manifested mainly in learning activities and methodology, with the characteristics and assumptions of the hermeneutic interpretive position curriculum. Moreover we can consider that the modules despite their particularities and differences in their teaching and learning, with characteristics saved approximation pedagogical approach that suggests the curriculum. We conclude that it is not explicit or clear the position that the teachers expressed regarding the pedagogical approach of the curriculum, so it is essential to deepen these concepts again with faculty. However, it is clear that significant progress has been made, however they must think that the investigation is unrelated to the nursing task, a finding consistent with the findings 12 years ago, when he became the curriculum change.